Key Success Factors and Risks for Hydrogen Based Road Transports - Gustafsson, Robin; Nicklasson, Alexander (My University, 2022)
Climate change is one of the world's most serious and defining challenges today, threatening mankind as a whole. Because today's transportation system is heavily reliant on fossil fuels, the present transportation sector is a significant contributor to the problem. To substitute fossil fuels, one solution is to use renewable hydrogen as a power source for vehicles. The hydrogen is being transformed into electricity through a fuel cell onboard the vehicle and the only emission is water, making this a both emission-free and renewable solution. The aim of this report has been to identify key success factors and risks that could affect the further development of a hydrogen based road transport sector through the whole value chain. By reviewing previous hydrogen based road transport projects, interviewing industry experts and conducting a workshop, we have identified factors and risks that should be considered for future projects. These are; - It is concluded that a collaboration between the stakeholders is needed. Many of the risks we have identified are common to the entire value chain. - Public support is needed, financially and by establishing a framework to support the development. - A cross-sectoral integration would decrease the costs along the value chain due to increased usage. - Ambitious and engaged stakeholders will benefit the development. - Stakeholders within the hydrogen transport sector need to be aware that there might be a conflict of interest between the Ministry of Finance and the Ministry of the Environment, due to the current tax system and the high revenues from the fossil-based transport sector.
Keywords: hydrogen; transportation; value chain; cross-sectoral integration; FCEV